2019
DOI: 10.1111/clr.13523
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trends in implant therapy at a surgical specialty clinic: Patient pool, indications, surgical procedures, and rate of early failures—A 15‐year retrospective analysis

Abstract: Objectives To evaluate the patient population over a 3‐year period and to compare it to observations of the population at the same clinic over a period of 15 years. Material and Methods Records of patients receiving dental implants in the Department of Oral Surgery and Stomatology, University of Bern, between January 2014 and December 2016 were analyzed and then compared with data from patients treated between 2002 and 2004 and between 2008 and 2010. Patients were analyzed for demographics and for indications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
1
20
0
6
Order By: Relevance
“…In this study, the early implant failure was defined as implant failure before the placement of final prosthesis 5 . Implant position was categorized as in anterior jaw (canine to canine) and in posterior jaw (premolars and molars) 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the early implant failure was defined as implant failure before the placement of final prosthesis 5 . Implant position was categorized as in anterior jaw (canine to canine) and in posterior jaw (premolars and molars) 10 …”
Section: Methodsmentioning
confidence: 99%
“…Since 1980s, there have been a series of studies investigating the early implant failure, with prevalence reported ranging from 0.3% to 5.8% at implant level 3‐7,9‐14 . However, a huge sample size divergence exists in previous studies (ranging from 186 patients to 30 959 implants), which jeopardizes the consistency of the reported conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, implant‐supported treatment solutions have become a predictable and viable option for prosthetic rehabilitation of toothless and partially edentulous patients. In this respect, titanium dental implants have been well documented over a long period of time and are widely accepted as the gold standard in contemporary dental implantology (Buser et al., 2012; Chiapasco et al., 2020; Chrcanovic et al., 2020; Ducommun et al., 2019; Jung et al., 2012; Pjetursson et al., 2012). Regardless of the reported success rates for dental implants, the implications of implant failure can be both medically and financially challenging (Mardinger et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The use of endosseous dental implants to support restorations replacing missing teeth has become well established since the introduction of titanium dental implants ( 1 , 2 ). The successful incorporation and rigid fixation of an implant within the surrounding bone was defined as osseointegration ( 3 ).…”
Section: Introductionmentioning
confidence: 99%